Evaluation of flucetosulfuron and ready-mix of penoxsulam + bentazone as post-emergent weed control options in direct seeded and transplanted rice - Chhokar, Rajender Singh; Sharma, Ramesh Kumar; Gill, Subhash Chander; Chaudhary, Ankur; Singh, Ram Kumar (Journal of Cereal Research, 2019)
Post-emergent herbicides were evaluated in a series of field experiments for control of weeds in rice nursery as well as, direct seeded and transplanted rice during the kharif seasons of 2014 and 2015. Results of one of the studies showed that flucetosulfuron at 25-30 g ha-1 applied at 15-18 DAS (days after sowing) was effective for control of many broad-leaved weeds and some grass weeds [Echinochloa crus-galli (L.) Beauv.]. However, flucetosulfuron was not reasonably effective against major upland rice weeds namely Dactyloctenium aegyptium (L.) Willd and Digitaria sanguinalis (L.) Scop. infesting rice nursery and direct seeded rice (DSR). Under puddle transplanted rice (PTR) conditions, flucetosulfuron 25-30 g ha-1 applied at 15-19 days after transplanting had similar weed control levels and rice grain yields as obtained with bispyribac-Na at 20 g ha-1 and azimsulfuron at 35 g ha-1. However, in the DSR, weed control and rice grain yields with flucetosulfuron were poorer to that observed with application of azimsulfuron 35 g ha-1. In another field study, ready-mixture of penoxsulam + bentazone (1:36) at 840-1110 g ha-1 as post-emergent (18 DAS or 20 DAT) option was evaluated against weeds in DSR and PTR along with standard check herbicides, azimsulfuron 35 g ha-1, and cyhalofop-p-butyl 80 g ha-1. Penoxsulam + bentazone at 925-1110 g ha-1 was very effective for control of grass weed, E. crus-galli (98-100% control) and many broad-leaved weeds but was not effective against D. aegyptium and D. sanguinalis found in DSR. Consequently, the poor weed control (508-524 g m-2 total weed dry weight) with application of penoxsulam + bentazone combination at 925-1110 g ha-1 resulted in 1.45-1.48 t ha-1 lesser grain yield compared to azimsulfuron 35 g ha-1 (218.2 g m-2 total weed dry weight). Under puddle transplanted conditions, penoxsulam + bentazone combination and azimsulfuron 35 g ha-1 provided significantly better weed control than cyhalofop-p-butyl. The weed competition caused higher rice grain yield reductions in DSR (86-100%) than PTR conditions (25-52%). The results indicated azimsulfuron as better herbicide option for DSR than flucetosulfuron, penoxsulam, penoxsulam + bentazone and bispyribac-Na due to diverse weed flora control. Also, pot studies indicated that flucetosulfuron and azimsulfuron should be applied with cationic surfactant at 1000 ml ha-1 for better weed control efficacy. DOI: http://doi.org/10.25174/2249-4065/2019/96493